Estimating the excess of inappropriate prescriptions of anti‐dopaminergic anti‐emetics during acute gastroenteritis epidemics in France. (12th August 2013) - Roussel, Victoire; Tritz, Thomas; Souty, Cécile; Turbelin, Clément; Arena, Christophe; Lambert, Bruno; Lillo‐LeLouët, Agnès; Kernéis, Solen; Blanchon, Thierry; Hanslik, Thomas
ABSTRACT Purpose Anti‐dopaminergic anti‐emetics (ADA) use for the treatment of nausea associated with gastroenteritis (GE) can be considered inappropriate, as their effects are not supported by evidence of clinical efficacy and can potentially induce serious adverse events. Objective This study quantifies the suboptimal consumption of ADA attributable to seasonal GE epidemics in France and its cost. Methods GE epidemiological data were collected and transmitted by the general practitioners (GPs) of Sentinelles network. Epidemic periods were identified by periodic regression. Drug sales data were obtained from pharmacies, and costs data were obtained from the French National Social Security. The ADA use and costs incurred by seasonal GE epidemics were calculated. Results During the epidemic periods considered in this study, the median age of patients seen by GPs for GE was 24 years old. During each epidemic, a sale increase by 14% for domperidone, by 15% for metoclopramide and 30% for metopimazine was observed. The average cost attributable to seasonal GE epidemic was 5 030 000 Euros, of which 2 160 000 Euros were incurred by the French National Social Security. Conclusion Linking epidemiological databases helped to identify and quantify inappropriate ADA prescriptions. GE treatment guidelines should be disseminated more widely. Copyright © 2013 John Wiley & Sons, Ltd.